Evaluating the potential of biodiesel production through microalgae farming in photobioreactor and high rate ponds from wastewater treatment - Pinho, David M. M. (2017)
In the last decade, the research works on microbial as a potential source of lipid for biodiesel production have been growing. In this work, the potential of a sludge from high-rate lagoons in urban sewage treatment, composed mainly by Chlorella sp., as oil source for biodiesel production, was studied. The potential of Chlorella sp. growth in photobioreactor under controlled conditions was also investigated. Low lipid content (up to 3%) was observed in both cases. The composition of both oils showed high amount of fatty acids and fatty acid based compounds, however there are also other non-fatty acid based lipids. Density and viscosity of biodiesel from biosolid oil were determined and the results showed that these physico-chemical properties do not match the specification required for biodiesel. The results showed that sewage sludge from Samambaia treatment station (DF, Brazil) and Chlorella sp. cultivated under the conditions described in this work are not potential sources of fatty material for biodiesel production.